The Use of Flashcards Through Umbul Game in Learning Vocabulary: Is It Effective? - Aris Ariyanto; Theresia Cicik Sophia B.; Sukma Nur Ardini (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
Vocabulary is the basic thing needed to learn the foreign language. It is wording that people have to know to communicate well, both in written and spoken structures, especially for young learners. Children's language development depends on their vocabulary, which has an impact on their academic performance. This study aimed to understand why first-grade elementary students struggle with English vocabulary in the curriculum. The primary goal was to determine if using flashcards with the Umbul game improved English vocabulary for first-grade students. The design of the research is Classroom Action Research (CAR). There are four fundamental processes in Classroom Action Research (CAR). Those are planning, acting, observing, and reflecting. In accordance with planning, the researchers prepare teaching kits needed to take action, such as: lesson plans, observation sheet, materials to be used in the classroom action, and evaluation sheet. In terms of acting, researchers implement the plan after preparing lesson plans, materials and evaluations. In this research, the researchers apply flashcards through Umbul games in teaching vocabulary. The researchers also give the post-test. Concerning observing, the researchers observe the process of teaching and learning activity. The researcher also makes result sheet to take note the information that occur during the activity. Regarding reflection, the researchers reflect, evaluate, and describe to improve the condition in the next cycle. The subjects were first-grade students from SD Pangudi Luhur Don Bosko Semarang participated in class I-C research projects. In this study, observation and evaluation sheet were applied as instruments. On the other hand, the information was obtained from observation and evaluation sheets. Information examined throughout the study was quantitative. The data was collected, and then it was examined by the researchers. The findings indicate a significant increase in first-grade students' motivation to learn English vocabulary, from 7% before to 15% after using flashcards. After implementing the flashcards through the Umbul game, the statistics indicated that students were able to acquire vocabulary with ease and were actively engaged in the teaching-learning process in the classroom. With the use of flashcards through Umbul games, students become more engaged in their studies and are more motivated to learn English. The students will have opportunities to improve their English by employing this strategy. Additionally, the English teacher can provide up chances for student participation in class activities by using flashcards as illustrated media. Hopefully, these findings can serve as a reference for future research.